2000
DOI: 10.3348/kjr.2000.1.3.121
|View full text |Cite
|
Sign up to set email alerts
|

Renal Artery Embolization Using a New Liquid Embolic Material Obtained by Partial Hydrolysis of Polyvinyl Acetate (Embol): Initial Experience in Six Patients

Abstract: ObjectiveTo evaluate the therapeutic efficacy of a new liquid embolic material, Embol, in embolization of the renal artery.Materials and MethodsEmbol is a new embolic material obtained by partial hydrolysis of polyvinyl acetate mixed in absolute ethanol and Iopromide 370 and manufactured by Schering Korea, Kyonggido, Korea. Six patients who underwent embolization of the renal artery using Embol were evaluated. Four were male and two were female and their ages ranged from 11 to 70 (mean, 53) years. Clinical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…For complete renal embolization, 0.2 ml/kg body weight of absolute ethanol (99% ethyl alcohol) is typically perfused in a mixture with non-ionic contrast material for appropriate control under fluoroscopy (Park et al. 1994;Park et al 2000). Vascular occlusion induced by the ethanol is more peripheral than most other agents (Latschaw1985).…”
Section: Absolute Ethanolmentioning
confidence: 99%
See 2 more Smart Citations
“…For complete renal embolization, 0.2 ml/kg body weight of absolute ethanol (99% ethyl alcohol) is typically perfused in a mixture with non-ionic contrast material for appropriate control under fluoroscopy (Park et al. 1994;Park et al 2000). Vascular occlusion induced by the ethanol is more peripheral than most other agents (Latschaw1985).…”
Section: Absolute Ethanolmentioning
confidence: 99%
“…A new liquid embolic material obtained by partial hydrolysis of polyvinyl acetate has been used recently (Park et al 2000).…”
Section: Other Embolic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The Expert Panel reviewed newly available studies since that assessment along with updated frequency and concentration of use information. [2][3][4][5][6][7][8][9][10][11] The Expert Panel confirmed that polyvinyl acetate is safe in the present practices of use and concentration given in Table 1 and did not reopen this safety assessment.…”
mentioning
confidence: 99%